2004
DOI: 10.1095/biolreprod.103.022533
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Semenogelin-Derived Peptides in the Antibacterial Activity of Human Seminal Plasma1

Abstract: Mechanisms for protecting spermatozoa, and the testes that produce them, from infection are essential, given the importance of these cells and organs for the fertility of the individual and perpetuation of the species. This is borne out by the publication of numerous papers on this subject over the last 50 years. We extended our work and that of others on the anti-infectious defense system of the male genital tract, using a new strategy for the direct identification of antibacterial molecules in human seminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 54 publications
0
46
1
2
Order By: Relevance
“…A correlation has been found between the degree of female promiscuity within a species and the evolution of the two genes encoding 3 semenogelins I and II, and thus it has been suggested that post-copulatory sperm competition drives the evolution of these genes [13,17,18]. In addition to having coagulum-forming functions and being susceptible to cleavage by kallikrein-like peptidases, the semenogelins are assumed to activate sperm hyaluronidase [19], affect sperm motility [20], possess antimicrobial activity [21], serve as substrates for transglutaminase [22], and have amyloid properties [23]. In short, it is suggested these two proteins participate in several steps that affect the ability of a spermatozoon to reach and fuse with an ovum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation has been found between the degree of female promiscuity within a species and the evolution of the two genes encoding 3 semenogelins I and II, and thus it has been suggested that post-copulatory sperm competition drives the evolution of these genes [13,17,18]. In addition to having coagulum-forming functions and being susceptible to cleavage by kallikrein-like peptidases, the semenogelins are assumed to activate sperm hyaluronidase [19], affect sperm motility [20], possess antimicrobial activity [21], serve as substrates for transglutaminase [22], and have amyloid properties [23]. In short, it is suggested these two proteins participate in several steps that affect the ability of a spermatozoon to reach and fuse with an ovum.…”
mentioning
confidence: 99%
“…The expression patterns of the small serine protease inhibitors are not restricted to the reproductive organs, and it has been suggested that these molecules play a role in the defense against a wide spectrum of microbes. Antimicrobial activity has also been proposed for the semenogelins [21]. Furthermore, the protein eppin, which is encoded in the whey-acidicprotein-type locus, has been identified in complex with semenogelin I both in seminal plasma 5 and on the surface of spermatozoa [39].…”
mentioning
confidence: 99%
“…Sperm-anchored PLA 2 synthesizes arachidonic acid, which is converted to prostaglandin E 2 , a step leading to acrosome reaction. Sperm PLA 2 is also implicated in sperm-egg fusion (Yuan et al, 2003) and secreted PLA 2 stimulates cytokine release by immune cells (Granata et al, 2005), exerting antimicrobial action in the seminal plasma (Bourgeon et al, 2004;Weinrauch et al, 1996). Osteopontin is typically involved in cell adhesion, tissue remodeling and activation of intracellular signaling (Denhardt, 2004;Mazzali et al, 2002).…”
Section: Proteome Of Seminal Fluidmentioning
confidence: 99%
“…In this respect, we asked if polyamines influence the antimicrobial capacity of the human cathelicidin LL-37 (29,31) or complement-mediated killing by normal human serum (NHS), because certain polyamines, LL-37, and complement proteins can coexist during gonococcal infection (1,5). Polyamines are cationic compounds synthesized by all living organisms and are involved in key cellular functions, such as growth (e.g., putrescine), DNA and RNA binding (e.g., spermidine and spermine), and resistance to oxidative stress (e.g., cadaverine) (for a review, see reference 33).…”
mentioning
confidence: 99%